A Buffer-Stock Model for the Government : Balancing Stability and Sustainability - Fournier, Jean-Marc (IMF Working Papers; Working Paper ;, 2019)
A fiscal reaction function to debt and the cycle is built on a buffer-stock model for the government. This model inspired by the buffer-stock model of the consumer (Deaton 1991; Carroll 1997) includes a debt limit instead of the Intertemporal Budget Constraint (IBC). The IBC is weak (Bohn, 2007), a debt limit is more realistic as it reflects the risk of losing market access. This risk increases the welfare cost of fiscal stimulus at high debt. As a result, the higher the debt, the less governments should smooth the cycle. A larger reaction of interest rates to debt and higher hysteresis magnify this interaction between the debt level and the appropriate reaction to shocks. With very persistent shocks, the appropriate reaction to negative shocks in highly indebted countries can even be procyclical.